2006
DOI: 10.1007/s00259-006-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved tumour detection by gastrin receptor scintigraphy in patients with metastasised medullary thyroid carcinoma

Abstract: GRS had a higher tumour detection rate than SRS and PET in our study. GRS in combination with CT was most effective in the detection of metastatic MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…New approaches, such as gastrin receptor scintigraphy, are promising because of the high expression of the cholecystokinin 2 receptor in MTCs (31,32). However, because of the variation in biologic behavior of MTC, the future will reveal what the best imaging approach for these tumors will be.…”
Section: Discussionmentioning
confidence: 99%
“…New approaches, such as gastrin receptor scintigraphy, are promising because of the high expression of the cholecystokinin 2 receptor in MTCs (31,32). However, because of the variation in biologic behavior of MTC, the future will reveal what the best imaging approach for these tumors will be.…”
Section: Discussionmentioning
confidence: 99%
“…One study also examined the potential therapeutic effects of 90 Y-DTPA-MG0 leading to tumor stabilization at the cost of severe renal toxicity (27). Scintigraphic imaging studies of patients injected with 111 In labeled gastrin-like peptides, or octreotide, showed higher tumor detection rate using gastrin-than somatostatin-receptor images (94 vs. 41%) (35).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors can be targeted with gastrin analogues, e.g., Minigastrin-0 (MG0) (27). Targeting of CCK2/ gastrin receptors with radiolabeled gastrin-like peptides may be a tool for radionuclide imaging and therapy, as previously studied in TT (28)(29)(30)(31) Tc, has previously been studied clinically with promising results (27,29,(33)(34)(35). One study also examined the potential therapeutic effects of 90 Y-DTPA-MG0 leading to tumor stabilization at the cost of severe renal toxicity (27).…”
Section: Introductionmentioning
confidence: 99%
“…There was no Pearson correlation between the scan results and the grade of tumor differentiation, but this aspect appears to deserve more attention. In a similar comparative study of 29 patients with metastatic medullary thyroid cancer, Gotthardt et al (95) found that tumor detection with gastrin receptor scintigraphy was 94.2%, whereas with SRS the detection rate was only 40.7%, correlating with in vitro autography data.…”
Section: Smentioning
confidence: 56%